“THE ENDURING OPTIMISM OF SHAKESPEARE’S LEGACY IN THE 21 ST CENTURY” - Bakhranov Bekhruz Abduxalil o‘g‘li (TADQIQOTLAR.UZ, 2024)
Annotation: In this article, we explore the enduring optimism found in William Shakespeare’s works and how his legacy continues to resonate in the 21st century. Through an analysis of his themes, characters, and enduring messages of hope, we delve into the timeless relevance of Shakespeare’s writings and their ability to inspire and uplift audiences across cultures and generations.